Abrupt elevation of tumor marker levels in a huge splenic epidermoid cyst, a case report - Cai, Hao; Hei, Zhenyu; Liu, Guanghua; Zhao, Feng; Wang, Chunfeng; Guan, Wenbin; Ren, Gang; Zhou, Qing; Dong, Yi; Wang, Ying; Gong, Wei; Chen, Litian (Frontiers in Oncology, 2024)
Epidermoid cyst of the spleen is a rare disease, and relatively few cases were reported by literatures. Most published case reports provided inadequate information on the impact of splenic epidermoid cyst on tumor markers. A 32-year-old woman with a giant splenic epidermoid cyst was reported, for whom the serum concentration of a collection of tumor markers (CA19–9, CEA, CA125, CA242, and CA50) increased abruptly accompanied by left upper abdominal pain for 5 days. After comprehensive preoperative examination and multidisciplinary team discussion, we ruled out any concurrent malignancy and a laparoscopic total splenectomy was performed, during which the splenic cyst spontaneously ruptured unexpectedly. After surgery, the elevated serum tumor marker levels decreased sharply until reaching normal range 3 months later. Learning from the case, we conclude that interval monitoring of serum tumor markers is of critical value for patients with splenic epidermoid cyst. Abrupt elevation of tumor marker levels and abdominal pain may serve as signs of cyst rupture, which is strongly indicative of surgical intervention as soon as possible. Total removal of the splenic cyst is strongly suggested considering the recurrence and malignant potential of the splenic epidermoid cyst.